Padrões de uso de provérbios na sociedade brasileira - Vellasco, Ana Maria de Moraes Sarmento (Cadernos de Linguagem e Sociedade, 2010)
This paper is the result of an ethnographic research within the framework of Interactional Sociolinguistics. The main purpose was to study the patterns of the use of proverbs by the Brazilian society, through the analysis of the conditions of production and reception in which proverbs are used. The following three general assertions were postulated: (i) proverbs are used in the interactional process and establish a normative frame, in which the speaker assumes ascendancy over the interactant; such ascendancy comes from the traditional and the didactic senses inherent in proverbs; (ii) the persuasive function is a feature of the enunciation of a proverb and one of the components in the formation of the referred frame; and (iii) proverbs are used by Brazilians as a way to save face, to justify their beliefs and attitudes. The research was carried out face-to-face, through oral spontaneous interviews, in rural and urban areas of Brasília, the capital of Brazil, and in towns of the Federal District, and of the state of Goiás; and in the Southern of Rio de Janeiro area, in which the informants mentioned to me their most used proverbs as well as others that they could remember, illustrating the situations of use. In order for the sample to be significant, only native Brazilians, children of native Brazilians, born in the five regions of the country, were involved in the study, irrespective of gender, age, educational level and socioeconomic status. The analysis of the spontaneous conversational situations confirmed the postulated assertions.